1996
DOI: 10.1007/s002469900082
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome as a Factor Influencing Hemodynamic Response to Pulmonary Artery Banding

Abstract: The hemodynamic response to pulmonary artery banding (PAB) in relation to the preoperative pulmonary/systemic vascular resistance (Rp/Rs) ratio and to the timing of surgery, with special regard to Down syndrome, was investigated in 56 nonconsecutive pediatric patients aged 3 days to 6 months (mean 2.5 months) with simple and complex congenital shunt-related cardiac malformations. Among the non-Down patient group (39 patients; mean age 6.9 weeks) there was a good hemodynamic response in all but three cases, irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Indeed, previous studies have shown that DS individuals may have elevated peripheral vascular resistance 7 and reduced peripheral vasodilator response. 37…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that DS individuals may have elevated peripheral vascular resistance 7 and reduced peripheral vasodilator response. 37…”
Section: Discussionmentioning
confidence: 99%
“…4 Late presentation in patients with trisomy 21 is also unusual as the development of elevated pulmonary vascular resistance is more severe and rapid in these patients. 5,6 One of the factors that allowed this patient to progress relatively symptom-free into adulthood may have been the protective vasoconstrictive effect of hypoxia secondary to sleep apnea. Hypoxic vasoconstriction is a defining characteristic of the pulmonary circulation, and a study has indeed found vasoconstriction in the pulmonary vasculature during obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung biopsies at PAB, the index of pulmonary vascular disease was less than 1.4 in all patients, which classified them as operable on the basis of previous studies. 17,18 Five patients (3 AVSD cases (1, 4, 6), 2 VSD cases (13,14)) had PVOD. All AVSD patients with PVOD underwent PAB when they were older than 1.5 months, whereas all VSD patients with PVOD underwent PAB when they were older than 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…PAB was planned to be performed in early infancy (within 2 months after birth 13 in principle), and ICR approximately 1 year later. Most of the patients underwent lung biopsy during both PAB and ICR, but some who underwent biopsy only during PAB were also included in the study.…”
Section: Methodsmentioning
confidence: 99%